The Effect of Motivation and Physical Work Environment towards Work Satisfaction and Performance of Employees in Non Medical Support Section of Wangaya Public Hospital Denpasar - Luh Putu Sri Anggreni; Putu Ngurah Suyatna Yasa; Ni Wayan Sitiari (Jurnal Ekonomi dan Bisnis Jagaditha, 2019)
The aim of this research is to analyze and explain the influence of motivation and work environment toward satisfaction of work, to analyze and explain the influence of motivation and work environment toward employee performance, to analyze and explain how the satisfaction of work in mediation influence the motivation of employee performance, how the satisfaction of work in mediation influence the work environment of employee performance. To answer the problem, we conducted research with 30 respondents. Data were collected with questionnaire. The analysis technique used was Parsial Least Square (PLS) Version 20. Based on the results obtained, conclusions include motivation has a positive and significant influence on satisfaction of work. Work environment have positive influence and significant to on satisfaction of work. Meanwhile, motivation has no significant effect to the employee performance. Enviroment has a positive and significant influence on employee performance. Satisfaction of work has positive a influence and significant on employee performance. Satisfaction of work is partial mediation between motivation and employee performance at Sekretariat Daerah Kota Denpasar. Satisfaction of work is partial mediation between work enviroment and employee performance at Sekretariat Daerah Kota Denpasar.